2017
DOI: 10.1111/lcrp.12109
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the schema mode concept in personality disordered offenders

Abstract: Purpose A core element of Schema Therapy (ST) is ‘schema modes’ or fluctuating emotional states. ST assumes that particular personality pathology consists of specific combinations of maladaptive schema modes. There is confirmatory evidence for the modes hypothesized to be central to borderline and narcissistic personality disorder (PD) in non‐forensic patients. In this study, we tested three aspects of the construct validity of schema modes in cluster‐B personality disordered offenders, examining its factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…We used the short version (80‐item) of the self‐report Schema Mode Inventory (SMI; Lobbestael et al., 2010) to measure externalising and healthy schema modes. Previous studies (Keulen‐De‐Vos et al., 2017; Van Wijk‐Herbrink et al., 2017) have confirmed that externalising schema modes may be labelled as Angry Child (feeling and expressing anger in an excessive way), Enraged Child (losing control over angry feelings and attacking), Impulsive Child (acting impulsively to get what one needs), Undisciplined Child (acting like a spoiled child) and Bully and Attack mode (using unacceptable behaviour to get what one wants). Healthy modes have been labelled as Healthy Adult (or Healthy Adolescent; having awareness of one's needs and feelings, and moderating, nurturing or healing other modes) and Happy Child (experiencing pleasure and acting playful and carefree as core emotional needs are met).…”
Section: Methodsmentioning
confidence: 91%
“…We used the short version (80‐item) of the self‐report Schema Mode Inventory (SMI; Lobbestael et al., 2010) to measure externalising and healthy schema modes. Previous studies (Keulen‐De‐Vos et al., 2017; Van Wijk‐Herbrink et al., 2017) have confirmed that externalising schema modes may be labelled as Angry Child (feeling and expressing anger in an excessive way), Enraged Child (losing control over angry feelings and attacking), Impulsive Child (acting impulsively to get what one needs), Undisciplined Child (acting like a spoiled child) and Bully and Attack mode (using unacceptable behaviour to get what one wants). Healthy modes have been labelled as Healthy Adult (or Healthy Adolescent; having awareness of one's needs and feelings, and moderating, nurturing or healing other modes) and Happy Child (experiencing pleasure and acting playful and carefree as core emotional needs are met).…”
Section: Methodsmentioning
confidence: 91%
“…A total score for healthy modes ( k = 70 items) and unhealthy modes ( k = 10 items) were calculated. The short version of the SMI proved to be reliable and valid in forensic and non-forensic samples (Keulen-de Vos et al, 2017; Lobbestael et al, 2010; van Wijk-Herbrink et al, 2018). For example, internal consistencies for the subscales were good to excellent, with Cronbach’s alpha ranging from 0.69 to 0.96 (Keulen-de Vos et al, 2017).…”
Section: Methodsmentioning
confidence: 94%
“…Several studies have supported the use of schema therapy in offender populations. For example, studies have shown a relationship between unhealthy schema modes and criminal behavior (Keulen-de Vos et al, 2016), between schema modes and personality disorders (Keulen-de Vos et al, 2017), and between schema modes and recidivism risk (Bernstein et al, 2012; Chakhssi et al, 2014). To our knowledge, there are no studies yet on the impact of emotional states on therapy alliance in offender populations.…”
mentioning
confidence: 99%
“…Following the increasing popularity of ST within the forensic setting, research is growing with regard to validating the schema mode concepts and techniques in individuals with a diagnosis of anti-social personality disorder (ASPD) and/or psychopathy (Chakhssi et al, 2012;Lobbestael et al, 2009). For example, antisocial individuals have been found to score significantly higher on the vulnerable child, angry child, detached protector, punitive parent and bully/attack modes than healthy controls (Lobbestael et al, 2008) and the construct validity of schema mode models were partially supported for offenders diagnosed with ASPD, BPD or narcissistic PD (Keulen-de Vos et al, 2017). Other research has also made links between EMS and PD traits in offending populations (Gilbert and Daffern, 2013) as well as demonstrating a role for schema modes in retrospectively formulating violent crimes in terms of the emotional state of the perpetrator in both the build-up and at the time of the offence (Keulen-de Vos et al, 2016).…”
Section: Why Use Schema Therapy With Forensic Populations?mentioning
confidence: 99%